The Potential Roles of Exosomal miR-214 in Bone Metastasis of Lung Adenocarcinoma - Zhang, Jian; Wu, Jiangmei (Frontiers in Oncology, 2021)
Bone metastasis is closely related to the alterations of bone microenvironment. In this article, we hypothesize that exosomes may be involved in the “vicious circle” by transferring miR-214. miR-214 is highly expressed in lung adenocarcinoma, and is closely related to the degree of lung cancer progression. As a key regulator of bone homeostasis, miR-214 promotes osteoclast differentiation and mediates intercellular communication between osteoclasts and osteoblasts via the way of exosomal miRNA. Therefore, it is highly probable that exosomal miR-214 derived from lung adenocarcinoma may disrupt bone homeostasis by enhancing bone resorption. Exosomal miR-214 can be released by lung adenocarcinoma cells, enters peripheral circulation, and is taken up by osteoclasts, consequently stimulating osteoclast differentiation. The enhanced bone resorption alters the bone microenvironment by releasing multiple cytokines and growth factors favoring cancer cells. The circulating cancer cells migrate to bone, proliferate, and colonize, resulting in the formation of metastasis. Furthermore, osteoclasts derived exosomal miR-214 may in turn contribute to cancer progression. In this way, the exosomal miR-214 from osteoclasts and lung adenocarcinoma cells mediates the positive interaction between bone resorption and bone metastasis. The levels of exosomal miR-214 in the peripheral circulation may help predict the risk of bone metastasis. The exosomal miR-214 may be a potential therapeutic target for both prevention and treatment of bone metastasis in patients with lung adenocarcinoma.